Perspectives - Minguzzi, Silvia, author; Gravdahl, John, advisor; Tornatzky, Cyane, advisor; Risbeck, Phil, committee member; Moseman, Eleanor, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2014)
We see what we want to see. We perceive the world around us in our own way and sometimes our perception is far from how others might perceive it. We have got used to rely on our feelings and emotions when we see or judge something and sometimes this leads to the misinterpretation of the things around us, because feelings and emotions can't be objective. Perspective projection distortion is the inevitable misrepresentation of three-dimensional space when drawn or projected onto a two-dimensional surface. It is impossible to accurately depict 3D reality on a 2D plane. The main focus of my body of work is to apply my research on how the new technologies pushed the boundaries of perspective projection distortion in the digital art world. I use perspective projections in my work not only as a technique, but also as a philosophy. Being able of looking at the world from a different perspective, being able to challenge stereotypical perspective is a powerful way to fight inequality in our society: income inequality, gender inequality. Diversity can be as simple as a different point of view. I believe in the power of data, and in my work I always look for inspiration in different terrain: politics, economics, anthropology, psychology are my bread and butter. I believe that any modern artist needs to push the art forward, inventing, defining new paradigms of expression with powerful meanings. It can be done using new technology, or researching new techniques with old media. It is about the experience the artist delivers to the public - whether it is provocative, whether it changes how the viewer thinks, feels and views the world. This is what really matters, and it has nothing to do with the techniques that the artist chooses to use. Just as the development of acrylic paints in the 20th century did not mean that oil paints or even the practice of creating one's own paint from pigments fell out of practice, so it is with technology. Just as some artists paint in oils only or acrylics only, some create their work digitally. Image editing and graphic design software programs are yet another tool to add to the artist's palette. This is why in my work I try to use a wide range of media: from printmaking to digital fabrication, from graphic design and typography to motion graphic and projection.
Keywords: design; equality; gender; identity; multimedia; perspective